DI BALIK JABOTABEK: URBANISASI, KEKUASAAN, DAN POLITIK TATA RUANG DI MASA ORDE BARU - Siti Faizatun Nisa' (Lambung Mangkurat University, 2025)
This paper seeks to trace the process of the formation of the peri-urban region of Jakarta–Bogor–Tangerang–Bekasi, or what we now know as Jabotabek. The development of Jabotabek cannot be separated from the broader context of national development at the time, and more specifically, from the development of the capital city, Jakarta. Looking further back, the emergence of Jabotabek is also closely tied to the historical context of the New Order period. Two key findings emerge from this research. The first is that the trauma of 1965, the difficult conditions in rural areas, and the bargaining power of the city collectively drove the flow of urbanization toward Jakarta. As the population grew due to this urbanization, the Jakarta city government felt the need to expand its territory and establish new urban centers. Jakarta’s expansion was officially formalized through the concept of Jabotabek, which encompassed three neighboring regencies—Bogor, Tangerang, and Bekasi—in 1976. The second finding is that, following the formation of Jabotabek, the intensity of development—particularly in housing complexes—increased significantly. Property developers played a major role in determining land management in the peri-urban areas of Jabotabek. Their close ties with political power enabled developers to create new towns that were modern, luxurious, and expensive. Furthermore, development in Jabotabek also generated processes of gentrification.